Algorithm For Nonlinear Transformations Of Local Contrasts - et. al., D. T. Muhamadiyeva, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Enhancing contrast is one of the important tasks of image processing, pattern recognition and machine vision. The solution to this problem directly related to an increase in the likelihood of correct image perception. The paper presents fuzzy methods for improving images, which based on nonlinear transformations of local contrasts, taking into account the peculiarities of human vision.